Evolusi Kurikulum Bahasa Arab untuk Tujuan Khusus (ASP) di Era Ekonomi Global - Atika Rismayasari; Agus Yasin (Institut Agama Islam Sunan Giri Ponorogo, 2026)
The era of the global economy has shifted the function of the Arabic language from a theological tool to a strategic asset in economic diplomacy; however, higher education institutions remain trapped in a rigid, classical-grammatical approach, leading to stagnation in pedagogical innovation and a mismatch between graduates’ competencies and professional sector needs. This study aims to analyze the transformation of labor market needs and formulate a model for reconstructing the Arabic for Specific Purposes (ASP) curriculum that is responsive to contemporary global economic dynamics through a descriptive-analytical qualitative approach with an evaluative-evolutionary design. Data were collected through document analysis and in-depth interviews with key informants, which were then analyzed using the Target Situation Analysis (TSA) and Present Situation Analysis (PSA) frameworks. The research findings reveal that the existing curriculum is still significantly dominated by theoretical material compared to professional simulations; thus, this study proposes an “Integrative-Adaptive ASP Curriculum” model that synergizes specific linguistic competencies with digital economic literacy and the integration of Artificial Intelligence (AI) to strengthen mastery of functional corporate discourse. As a concrete recommendation, higher education institutions are encouraged to reorient their curricula through strategic collaboration with industry practitioners and to transform the role of instructors into multidisciplinary mentors to ensure the relevance of graduates in the global market.